Application of sustainability concept in selected sub-regions: the case of Finland as member of the European Union - Owusu Aning, George (Univerzita Pardubice, 2020)
The aim of this work was to identify the specific programmes embarked on by the Finnish government in chalking the success in sustainable development, and to highlight the thematic areas measurable in line with the Sustainable Development Goals. The work was partially theoretical analysis of sustainable development in the study area. The research arrived at its objective through the use of secondary sources of data analysed qualitatively. Data on sustainable development from local (Finland) regional (EU) and international (UN and its bodies, and OECD) levels were accessed and assessed to allow for a comprehensive conclusion with regard to the country's local efforts and programmes that guide their commitment to the SDGs. Social and academic programmes were the channels through which sustainable development ideas are inculcated into the public. Finland has been successful in all the thematic areas that were investigated, standing tall among countries in the World development. The country's effort towards sustainable development permeates every aspect of their local, regional, and state level policies. The office of the prime minister is the spearhead for the agenda, its commitment and readiness to enhance the campaign is evident in the policies of both private and public organizations. Sustainable development policies are consciously interspersed in policies of sector ministries. Among the various themes where sustainable development was practically measured were climate change, relative to renewable consumption and production, energy efficiency and sustainable usage of ecosystem services. Other areas include assessments based on the following dimensions of human well-being and societal development; sustainable society index (SSI), World happiness index (WHI), the World's most literate Nations, corruption perception index (CPI), good country index (GCI), fairness for children, and open data index (ODI).
Keywords: udržitelný rozvoj; ekonomická udržitelnost; environmentální udržitelnost; sociální udržitelnost; Finsko; pilíře udržitelného rozvoje; sustainable development; economic sustainability; environmental sustainability; social sustainability; Finland; pillars of sustainable development